Mortality and morbidity of neonatal shock in premature babies in a tertiary care neonatal intensive care unit - Shah, Mubashir Hassan; Roshan, Reashma (International Journal of Contemporary Pediatrics, 2021)
Background: Despite advances in understanding of pathophysiological changes in neonatal shock, its effect on morbidity and mortality is still an ongoing process. The primary objective was to study etiology-specific mortality and the secondary objective was to study the short-term morbidities of neonatal shock in premature babies born less than 34 weeks of gestation. Methods: This single centre prospective cohort study was conducted from 01 January 2017 to 31 March 2018. Neonatal shock was defined on clinical and laboratory criteria. Outcomes in terms of mortality and short-term morbidities like intraventricular hemorrhage (IVH), necrotizing enterocolitis (NEC), acute kidney injury (AKI), chronic lung disease (CLD) and retinopathy of prematurity (ROP) were recorded for analysis. Results: A total of 119 preterm neonates with shock were enrolled. The most common etiology of neonatal shock was late-onset-sepsis (LOS: 34.4%; n=41) followed by transient circulatory compromise (22.6%; n=27) and early-onset-sepsis (EOS: 14.2%, n=17). The overall mortality of neonatal shock was 15.9% (n=19) out of which 36.8% (n=7) had EOS, 26.3% (n=5) had myocardial dysfunction and 21% (n=4) had LOS (p<0.05). On logistic regression, none of the independent variables were significant for mortality. Neonatal morbidities of IVH (> Grade 2), NEC, CLD, AKI and ROP developed in 4.2% (n=5), 11.7% (n=14), 15% (n=18), 27.7% (n=33) and 33. 6% (n=40) respectively. Conclusions: LOS was the commonest etiology of neonatal shock in preterm neonates. Neonatal shock due to EOS was the major cause of mortality in preterm neonates thus highlighting the need for preventing EOS to improve survival and to reduce neonatal morbidities.